Probiotic-mediated modulation of gut microbiome in students exposed to academic stress: a randomized controlled trial - Jorge Francisco Vázquez-Castellanos; Lucas Ferreira Maciel; Lucas Wauters; Ann Gregory; Lukas Van Oudenhove; Karlien Geboers; Kristin Verbeke; Tamara Smokvina; Jan Tack; Tim Vanuytsel; Muriel Derrien; Jeroen Raes (npj Biofilms and Microbiomes)
Abstract Probiotics have been widely tested for their effect on mental well-being, albeit with heterogeneous outcomes. Direct and indirect effects through the gut microbiome might lie at the basis of these observations. Here, in a post-hoc analysis, we assessed the effect of 4-week consumption of a probiotic candidate strain on the gut microbiome in students exposed to academic stress. Healthy students were randomized to consume a fermented milk product with Lacticaseibacillus rhamnosus CNCM I-3690 (N = 39) or an acidified non-fermented milk product (N = 40) twice daily for 4 weeks before academic exams. The gut microbiome was analysed by Quantitative Microbiome Profiling based on 16S rRNA gene amplicon and shotgun metagenomic sequencing. Stress and anxiety were assessed using both objective and self-reported markers. Changes of alpha-diversity markers and community shifts from baseline (beta diversity) were lower in L. rhamnosus treated individuals over controls, suggesting lower overall changes of gut microbiota during psychological stress in the Probiotic group. The intake of L. rhamnosus CNCM I-3690 induced differential abundance of some species, such as the maintenance of the quantitative abundance of Ruminococcus bicirculans, and co-varied with species, which differed according to visits (i.e., stress level), suggesting a potential beneficial effect of the strain before the highest increase of stress level. The higher quantitative abundance of F. prausnitzii induced by the probiotic intake was associated with lowered self-reported anxiety levels before the exam. Functional analysis revealed minor changes upon intake of the probiotic strain. Taken together, using a quantitative framework, we found that L. rhamnosus CNCM I-3690 has a potential effect on gut microbiome response to stress, although further studies are needed to better understand the precise interaction.